IMPLEMENTATION OF THE UNIFORM DOMAIN NAME DISPUTE RESOLUTION POLICY IN THE RESOLUTION OF DOMAIN NAME DISPUTES AS A FORM OF TRADEMARK PROTECTION - Fatma Putri Fadilah; Ema Nurkhaerani (Zhata Institut, 2025)
The growth of the digital economy has made domain names a valuable asset for brands, but it has also given rise to cybersquatting practices that cause disputes between brand owners and unauthorized domain registrants. This study analyzes the application of the Uniform Domain Name Dispute Resolution Policy (UDRP) in resolving domain name disputes as a form of trademark protection in Indonesia, with a case study of PPND Decision Number 054-0525 regarding the domain lippo.co.id. The research method uses a normative juridical approach using a statute approach, a conceptual approach, and a case approach. The results show that the UDRP, adopted through the PPND Policy by PANDI, applies three main elements of proof: similarity between the domain and the registered trademark, absence of legitimate rights of the registrant, and bad faith. In the case of lippo.co.id, the PPND Panel decided to transfer the domain to the legitimate trademark owner because it was proven to meet all three elements. The criteria for bad faith are assessed based on objective and subjective indicators, including public deception and financial gain motives. This study recommends harmonizing the PPND policy with the Trademark Law, increasing awareness of dispute resolution mechanisms, and strengthening the synergy between PANDI and DJKI. Keywords: Cybersquatting; Domain Name; Trademark Protection.